2004
DOI: 10.1080/13554790490507650
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Recall and Recognition Memory Performance in an Amnesic Patient with Hippocampal Damage Following Carbon Monoxide Poisoning

Abstract: Some patients with relatively selective hippocampal damage have shown proportionate recall and recognition deficits. Moreover, familiarity as well as recollection have been found to be impaired in some of these patients. In contrast, other patients with apparently similar damage presented with relatively preserved recognition despite having severely impaired recall, and some of these patients have been shown to have preserved familiarity. We report here the case of an amnesic patient who suffered bilateral hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 53 publications
11
64
0
3
Order By: Relevance
“…On the one hand, there is considerable evidence that recognition memory, like other declarative memory abilities (e.g., recall memory), is impaired by either MTL or diencephalic damage (Haist et al 1992;Reed and Squire 1997;Kopelman and Stanhope 1998;Manns et al 2003;Zoppelt et al 2003; Cold Spring Harbor Laboratory Press on May 13, 2018 -Published by learnmem.cshlp.org Downloaded from Wais et al 2006) (also a single case, RG [Kishiyama et al 2005]). On the other hand, some studies have reported that recognition memory is normal (or near normal) following damage to these regions (Aggleton and Shaw 1996;Turriziani et al 2004) (also the single cases ROB [Hanley et al 2001], YR [Holdstock et al 2002], MR [Bastin et al 2004], and KN [Aggleton et al 2005]). …”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there is considerable evidence that recognition memory, like other declarative memory abilities (e.g., recall memory), is impaired by either MTL or diencephalic damage (Haist et al 1992;Reed and Squire 1997;Kopelman and Stanhope 1998;Manns et al 2003;Zoppelt et al 2003; Cold Spring Harbor Laboratory Press on May 13, 2018 -Published by learnmem.cshlp.org Downloaded from Wais et al 2006) (also a single case, RG [Kishiyama et al 2005]). On the other hand, some studies have reported that recognition memory is normal (or near normal) following damage to these regions (Aggleton and Shaw 1996;Turriziani et al 2004) (also the single cases ROB [Hanley et al 2001], YR [Holdstock et al 2002], MR [Bastin et al 2004], and KN [Aggleton et al 2005]). …”
Section: Discussionmentioning
confidence: 99%
“…Studies of developmental as well as adult-onset amnesia have reported cases in which hippocampal damage produced intact recognition memory but impaired episodic memory, or the ability to recollect information pertaining to the specific event during which the stimulus was first encountered (11,12,15,18, but see also 6). The "RememberKnow" procedure has often been used to try to distinguish impairments in simple recognition from deficits in recall (12,15,(19)(20)(21). However, this depends on the assumption that Remember judgments reflect recollection while Know judgments reflect familiarity.…”
mentioning
confidence: 99%
“…Although a number of studies have found that amnesic patients show equivalent impairments in recall and recognition tasks (Haist, Shimamura, & Squire, 1992;Kopelman & Stanhope, 1998;MacAndrew, Jones, & Mayes, 1994;Manns, Hopkins, Reed, Kitchener, & Squire, 2003), others have reported that the impairment in amnesia is less severe in recognition than in recall tasks (Bastin et al, 2004;Hirst, Johnson, Phelps, & Volpe, 1988;Hirst et al, 1986;Yonelinas et al, 2002). Moreover, some researchers have reported that recognition memory may be entirely spared in amnesic patients with circumscribed hippocampal lesions (Aggleton & Shaw, 1996;Aggleton et al, in press;Mayes, Holdstock, Isaac, Hunkin, & Roberts, 2002;Vargha-Khadem et al, 1997;see also Barbeau, Felician, Joubert, Sontheimer, Ceccaldi, & Poncet, 2005), although this is not always the case (Manns & Squire, 1999;Manns et al, 2003;Reed & Squire, 1997).…”
Section: Introductionmentioning
confidence: 99%